Applied survey data analysis - Heeringa, Steven; West, Brady T.; Berglund, Patricia A. (Boca Raton, FL : Chapman & Hall/CRC, 2010)
The book provides a statistical overview of the analysis of complex sample survey data. It contains features of complex sample designs and shows how to intergrate design characteristics into statistical methods. It also includes software for survey estimation and interference.
Includes bibliographical references and index.
opc 29/04/13
Loan
Keywords: Social sciences; Social surveys